A comparative performance analysis of accident anticipation with deep learning extractors - Mostak, Alfi Mashab; Neha, Nayna Jahan; Mohiuddin, Azwaad Labiba; Tabassum, Adiba (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.